2016
DOI: 10.1016/j.jlumin.2015.08.055
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Eu3+ substitution sites and photoluminescence properties of SrIn2O4:Eu3+ spinel phosphors

Abstract: Eu 3+-doped SrIn2O4 phosphors were synthesized by the solid solution method at 1400 ºC in air. The chemical composition of the phosphors was systematically changed to study the relation between the Eu 3+ substitution site and photoluminescence (PL) properties. Under excitation of the 7 F0→ 5 L6 transition of Eu 3+ at 393 nm, the SrIn2O4:Eu 3+ exhibited dominant red emission peaks at 611, 616 and 623 nm, which are attributed to the electric dipole transition 5 D0→ 7 F2 of Eu 3+. The results of X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…CaFe 2 O 4 -type structure has columns of edge-sharing double octahedra along the b axis (Figure ), which indicates possible oxide-ion conduction along the columns in the b direction, due to the movement of oxide ions along the edges of octahedra. We have focused on the CaFe 2 O 4 -type oxides because of (i) the possible oxide-ion conduction and (ii) good thermal and chemical stability. Numerous researchers have investigated the optical, electrical, and magnetic properties of CaFe 2 O 4 -type materials. However, to our best knowledge, pure oxide-ion conduction has not been shown in CaFe 2 O 4 -type materials. Kharton et al and Tsipis et al reported that CaFe 2 O 4 is a mixed electronic and oxide-ion conductor and that its total conductivity is predominantly electronic.…”
Section: Introductionmentioning
confidence: 99%
“…CaFe 2 O 4 -type structure has columns of edge-sharing double octahedra along the b axis (Figure ), which indicates possible oxide-ion conduction along the columns in the b direction, due to the movement of oxide ions along the edges of octahedra. We have focused on the CaFe 2 O 4 -type oxides because of (i) the possible oxide-ion conduction and (ii) good thermal and chemical stability. Numerous researchers have investigated the optical, electrical, and magnetic properties of CaFe 2 O 4 -type materials. However, to our best knowledge, pure oxide-ion conduction has not been shown in CaFe 2 O 4 -type materials. Kharton et al and Tsipis et al reported that CaFe 2 O 4 is a mixed electronic and oxide-ion conductor and that its total conductivity is predominantly electronic.…”
Section: Introductionmentioning
confidence: 99%
“…A theoretical analysis of the TL phenomenon was done for the first time by Randall and Wilkins . According to their model, electrons are trapped during γ‐irradiation at some lattice sites.…”
Section: Resultsmentioning
confidence: 99%
“…In the SrIn 2 O 4 structure, there are octahedral chains of InO 6 , which give this material good photocatalytic and luminescent properties due to a possible mobility of charge carriers [13]. Kang et al [14] obtained SrIn 2 O 4 doped with Eu 3 + and studied the photoluminescent properties in the application of red phosphors to white LED's. Wang and Tian [15] investigated the photoluminescent properties of SrIn 2 O 4 :Eu 3+ ,Gd 3+ e SrIn 2 O 4 :Eu 3+ ,Sm 3+ .…”
Section: Introductionmentioning
confidence: 99%